Adjuvant role of testosterone in treatment of schizophrenia and its interaction with combination of first and second generation anti-psychotics, chlorpromazine and risperidone - Vijaywargia, Tarun (International Journal of Basic & Clinical Pharmacology, 2018)
Background: There is great controversy about role of male sex steroid, testosterone, in mental disorders like schizophrenia. This study assessed the effectiveness of testosterone in schizophrenic patients and probes how it modulates the action of combination of first and second generation anti-psychotic medications (Chlorpromazine + Risperidone) both of which are very commonly used anti-psychotic agents in clinical psychiatric practice. Methods: It Is randomized, double-blind, Clinical study performed in Indian schizophrenic patients (new cases) in the Department of psychiatry from Feb 2003 to March 2004. Patients twelve (12) patients aged 20 to 60 years diagnosed schizophrenics according to ICD-10 Criteria who visited in outpatient department of psychiatry during study period. 12 Patient was treated with combination of oral Chlorpromazine 200mg BD + oral Risperidone 2mg BD, half of the 12 patients also received single dose of testosterone 100mg intramuscularly with above-mentioned treatment. Measure How symptomatology in schizophrenic patients affected is measured by applying various validated psychiatric scales like Brief psychiatric Rating Score (BPRS), Scale for assessment of positive symptom(SAPS), and Scale for Assessment of Negative Symptoms (SANS). Results: Single dose of Testosterone 100mg administered initially by I.M. route potentiated the reduction level in negative symptoms of schizophrenia by 119% in patients receiving oral Chlorpromazine 200mg along with oral Risperidone 4mg/day. Conclusions: In this study, Testosterone potentiated the effects of combination of oral Chlorpromazine 100mg BD + Risperidone 2mg BD, on general psychotic manifestations, positive symptoms and negative symptoms of schizophrenia, assessed on BPRS, SAPS and SANS scoring scales, however the effect is most pronounced in negative symptomology of schizophrenia.